Temporal expression of heat shock genes during cold stress and recovery from chill coma in adult Drosophila melanogaster. - Colinet, H.; Lee, S.F.; Hoffmann, A. (FEBS Journal, 2010)
A common physiological response of organisms to environmental stresses is the increase in expression of heat shock proteins (Hsps). In insects, this process has been widely examined for heat stress, but the response to cold stress has been far less studied. In the present study, we focused on 11 Drosophila melanogaster Hsp genes during the stress exposure and recovery phases. The temporal gene expression of adults was analyzed during 9 h of cold stress at 0 degrees C and during 8 h of recovery at 25 degrees C. Increased expression of some, but not all, Hsp genes was elicited in response to cold stress. The transcriptional activity of Hsp genes was not modulated during the cold stress, and peaks of expression occurred during the recovery phase. On the basis of their response, we consider that Hsp60, Hsp67Ba and Hsc70-1 are not cold-inducible, whereas Hsp22, Hsp23, Hsp26, Hsp27, Hsp40, Hsp68, Hsp70Aa and Hsp83 are induced by cold. This study suggests the importance of the recovery phase for repairing chilling injuries, and highlights the need to further investigate the contributions of specific Hsp genes to thermal stress responses. Parallels are drawn between the stress response networks resulting from heat and cold stress.